Contribution of Startup Studios in Entrepreneurship in Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study aims to reveal the degree of contribution of the startup studio to entrepreneurship, and to find statistically significant differences at the significance level between the arithmetic means of the study individuals' responses about the startup studio from the perspective of entrepreneurs in the Kingdom of Saudi Arabia and attributed to the variables (age, type of entrepreneur: participant in a studio, independent entrepreneur). The study relied on the descriptive comparative approach, and the questionnaire as a study tool and was applied to (53) members of the study community of entrepreneurs in Riyadh in the Kingdom of Saudi Arabia.The study concluded that the study individuals from entrepreneurs in Riyadh in the Kingdom of Saudi Arabia believe that the contribution of the startup studio to entrepreneurship is high. It also concluded that there are statistically significant differences in the arithmetic means of the study individuals' responses towards the dimensions (infrastructure, business support, access to networks) according to the variable of entrepreneur type, where the significance levels reached (0.01), that these differences are in favor of the study individuals from entrepreneurs participating in the startup studio. In light of the results, a number of recommendations were made, the most important of which is to increase the number of startup studios in different regions and sectors to serve entrepreneurs and startups in various fields to transfer expertise and provide guidance. Among the recommendations is the need for government agencies and large institutions to adopt the idea of ​​the startup studio to be a link with entrepreneurs and startups and to enhance innovation in the institution.
Keywords: Startup Studio; Entrepreneurs; Entrepreneurship; Kingdom of Saudi Arabia